Por um indicador de letramento digital: uma abordagem sobre competências e habilidades em TICs - Rosa, Fernanda Ribeiro (2012)
This thesis’s main objective is to begin the development of a new indicator, called initially as 'Digital Literacy Index' (DLI). This indicator aims at shifting the debate away from the issue of access to information and communication technologies, in order to focus on their use and the competencies that are associated with it. Its approach differs from metrics that assess tool dexterity, because it is built on the social use of digital resources, and its benefits to daily life. Therefore, DLI measures a concept that has been defined as digital literacy, which means the condition that enables someone to take advantage of information and communication technologies in order to meet social environment needs. It also includes two dimensions that are part of the digital environment: 1) ICT operational skills, which involve the knowledge to handle technologies and their tools, in order to take any action in a digital environment; 2) ICT informational skills, or the capacity to handle and integrate information from different levels and of different formats in a digital environment, so that it can be transformed into useful content that responds to an individual’s purpose, in addition to the ability to evaluate information and situations to which one is exposed while using ICT and to understand the operational standards that enable someone to act autonomously in this environment. At the end, this paper presents a rubric with its respective descriptors and a detailed definition of the areas that they cover, using as references not only interviews with specialists, but also rubrics that already exist in Brazil and other countries, and that address ICT`s technical/operational dimension, and the literacy model by Eshet-Alkalai, which is applied to ICT`s informational dimension. We conclude this work by highlighting some of the challenges and key issues that must be addressed in order to continue the development of this indicator.